The association of different types of physical activity and diabetes co-morbid depression: A cross-sectional analysis - Yage Yang; Hongzhen Liu (PLoS ONE, 2025)
Background Diabetes co-morbid depression is a significant public health burden. Physical activity (PA) has been suggested as a potential approach to reduce the risk of diabetes co-morbid depression. Different types of PA may have different effects on diabetes co-morbid depression. Objective The aims of this study were to investigate the association between moderate to vigorous physical activity (MVPA), different types of physical activity, including work activity (WPA), transportation physical activity (TPA), recreational physical activity (RPA), sedentary behavior (SB), and co-morbid depression in participants with diabetes. Materials and methods The data for this study were derived from the 2017-2018 National Health and Nutrition Examination Survey (NHANES). A total of 642 participants aged 20 years and above were included in the study (mean age: 63.54 ± 12.08 years; 367 males and 275 females). Depression was screened by PHQ-9 in participants who were told to have diabetes by a doctor. PAs were screened by GPAQ. A binary logistic regression model was performed to analyze the association of RPA and diabetes co-morbid depression. Results The causal relationship between MVPA and diabetes co-morbid depression did not reach a significant level (P=0.949), nor did it reach in WPA (P=0.203), TPA (P=0.299) and SB (P=0.219). RPA had a significant effect on diabetes co-morbid depression (OR=0.508, 95%CI: 0.347-0.742, P<0.001), the effect remained significant after adjusted for confounding variables (OR=0.522, 95%CI: 0.356-0.789, P=0.002). Conclusions Among the various types of physical activity, only RPA was a protective factor for co-morbid depression in diabetes.